Psychotherapies for posttraumatic stress disorder applied for people in indonesia: A scoping review - Ninik Yunitri; Christina Yeni Kustanti; Fauzi Ashra; Slametiningsih Slametiningsih; Nuraenah Nuraenah; Rani Septiawantari; Nurlia Ikaningtyas (Faculty of Nursing Universitas Padjadjaran, 2023)
Background: Posttraumatic stress disorder (PTSD) occurs as triggered or exposure to traumatic events. Psychotherapies have been proven to be effective and superior for people with PTSD. Several psychotherapies have been developed with different approaches. Yet the application of psychotherapy is rarely found and provided by professionals to those who need it in Indonesia. Purpose: This study aimed to figure out the application of PTSD psychotherapies for people with PTSD based on studies conducted in Indonesia. Methods: The review was reported following the PRISMA statement for scoping reviews. A systematic screening was performed in CINAHL, Cochrane library, Embase, Portal Garuda, PubMed, Scopus, as well as manual searches without language and date restrictions. The quality of the study was determined based on the risk of bias. Cochrane risk of bias 2.0 (RoB 2.0) and MINORS were used to evaluate the risk of bias of RCT and quasi-experimental studies, respectively. Results: Five RCTs and four quasi-experimental studies published from 2008 to 2022 (n=465) were employed in this review. Three types of therapies were conducted for people with PTSD; five CBT studies, two EMDR studies, and two SHAT studies, performed in one day up to six weeks, one to 15 sessions, and 30 to 60 minutes for each session. All studies evaluated PTSD as the primary outcome, while the most measured secondary outcomes were depression and anxiety symptoms. Conclusions: CBT was the most frequent therapy for Indonesian people with PTSD, followed by EMDR and SHAT. The application of therapies varied in frequency, duration, length of therapy, and component. Further research on the implementation of various types of psychotherapy for people with PTSD will be required.